Analisis Peningkatan Kualitas Pelayanan Menggunakan Metode Service Quality (SERVQUAL) dan Importance Performance Analysis (IPA) (Studi Kasus di PDAM Kabupaten Banggai) - Nahri Sakinah, Nur'irni; Achmadi, Fuad; Septiari, Renny (JURNAL TEKNIK UNILAK, 2024)
The purpose of this study is to analyze service quality based on customer satisfaction and determine the factors that affect service quality to get solutions to the causes of problems based on service quality. This research will use the servqual method to measure service quality with the level of perceptions and expectations of consumers in the services provided by service providers. Furthermore, the Importance Performance Analysis (IPA) method is used in measuring the level of importance and performance so that companies can find out the attributes that need to be improved and maintained in services based on Cartesian diagrams and will produce a basis for customer satisfaction. After that, Fishbone Diagram is used to analyze the consequences by finding and describing the factors that cause existing problems. Then, improvement proposals are given and submitted by PDAM to be followed up by PDAM Kab.Banggai. The results of the Service Quality analysis of the quality of service of PDAM Kab. Banggai obtained a negative Gap in the Reliability dimension at attribute B5 (-1.200), in the Responsiveness dimension obtained a negative Gap at attribute C1 (-1.140), at attribute C2 with a negative Gap (-1.120) and in the Assurance dimension with a negative Gap (-0.560). The results of the analysis using Importance Performance Analysis obtained 4 attributes that are included in the top priority for improvement, namely the attributes contained in quadrant I. For further research, it is expected to conduct research to implement the proposed improvements given and analyze the quality of service after implementing the proposed improvements given by the author so that the effectiveness of the services that have been implemented can be known.